Urinary tract pathogens and their antimicrobial resistance patterns in Turkish children - ALPAY, HARİKA; GÖKCE, İBRAHİM (SPRINGER, 2006)
Urinary tract infections (UTIs) are among the most common bacterial diseases in childhood affecting approximately 3-5% of girls and 1% of boys [1]. There is growing concern regarding the resistance of urinary pathogens to commonly used antibiotics because of the increasing number of therapeutic failures after empiric treatment [2]. To ensure appropriate treatment, knowledge of the organisms that cause UTI and their antibiotic susceptibility is mandatory [3]. They need to be constantly reevaluated to achieve maximal clinical response before the antibiotic susceptibility of the isolate is known. The aim of this study was to assess the susceptibility of urinary pathogens to commonly used antibiotics in Turkish children with community- acquired UTI. Children who were admitted with the first episode of UTI to the Pediatric Outpatient Clinic and consulted to the Pediatric Nephrology Department between 2001 and 2003 were included in the study prospectively. UTI was defined as the growth of a single pathogen of greater than 100,000 colony-forming units/ml by a properly collected urine specimen in children with febrile disease or urinary symptoms. Transurethral catheterisation was chosen for children who were not toilet trained (387 children, 75.4% of all cases) and clean midstream specimen collection was preferred for toilet trained children. Antimicrobial susceptibility of the isolates was tested by the automatized identification technique called VITEK (bioMerieux, France). Five hundred thirteen uncomplicated community-acquired UTIs were detected in children aged 0-16 years (mean age 3.0 years); 271 (52.8%) of the children were female. The isolated microorganisms were Escherichia coli in 277 (54.0%), Klebsiella spp. in 88 (17.2%), Proteus spp. in 62 (12.1%), Staphylococci spp. in 31 (6.0%), Pseudomonas spp. in 15 (2.9%), Enterococcus spp. in 15 (2.9%), Enterobacter spp. in 13 (2.5%), and others in 12 (2.4%). Gram-positive cocci were isolated in 48 (9.3%) of UTIs. No vancomycin-resistant Enterococcus spp. were isolated. The antibiotic resistance patterns of different gram-negative pathogens are shown in Table 1. A high proportion of the isolates were resistant to ampicillin (69%), amoxicillin/clavulanate (44%), cefazolin (39%) and trimethoprim sulfamethoxazole (TMP-SMX) (32%). The most effective drugs against all the isolates were found to be cefepime (99%), cefixime (99%), ceftriaxone (90%), nitrofurantoin (83%) and cefuroxime (79%). There was no antimicrobial resistance to ciprofloxacin and aminoglycosides except in one case. In our study nearly half of the pathogens were resistant to amoxicillin/clavulanate and one-third of them were resistant to TMP-SMX which shows that empiric treatment with TMP-SMX and amoxicillin/clavulanate is inadequate. The results showing 21% resistance to cefuroxime, 17% resistance to nitrofurantoin and 1% resistance to cefixim led us to recommend these drugs for common treatment of UTI in Turkish children. Parenteral treatment options for treatment are second and third generation cephalosporins and aminoglycosides. Our results showed that resistance rates for these drugs are tolerable. Only 10% of the microorganisms displayed resistance to ceftriaxone and none of them showed resistance to aminoglycosides. In conclusion, longitudinal studies on the resistance patterns of antibiotics are needed so that appropriate recommendations can be made for the treatment and prophylaxis of children with UTI.